2014
DOI: 10.1261/rna.045823.114
|View full text |Cite
|
Sign up to set email alerts
|

Structure of RNA 3′-phosphate cyclase bound to substrate RNA

Abstract: RNA 3′ -phosphate cyclase (RtcA) catalyzes the ATP-dependent cyclization of a 3 ′ -phosphate to form a 2 ′ ,3 ′ -cyclic phosphate at RNA termini. Cyclization proceeds through RtcA-AMP and RNA(3 ′ )pp(5 ′ )A covalent intermediates, which are analogous to intermediates formed during catalysis by the tRNA ligase RtcB. Here we present a crystal structure of Pyrococcus horikoshii RtcA in complex with a 3 ′ -phosphate terminated RNA and adenosine in the AMP-binding pocket. Our data reveal that RtcA recognizes substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Predominant genome associations of RtcA with RtcB suggest that they might function together in 3′-end processing during RNA ligation (see discussion below). Additional roles for RtcA could include cyclic termini recognition/cyclic phosphate end maintenance, a possibility for eukaryotic RtcA acting on U6 snRNA ( 196 ).…”
Section: Major Classes Of Protein Domains Involved In Rna Repairmentioning
confidence: 99%
“…Predominant genome associations of RtcA with RtcB suggest that they might function together in 3′-end processing during RNA ligation (see discussion below). Additional roles for RtcA could include cyclic termini recognition/cyclic phosphate end maintenance, a possibility for eukaryotic RtcA acting on U6 snRNA ( 196 ).…”
Section: Major Classes Of Protein Domains Involved In Rna Repairmentioning
confidence: 99%
“…These findings were nicely complemented by structural analysis of the archaeon Pyrococcus horihoshi RtcA complexed with 3'-phosphate-terminated RNA, performed in Raines' laboratory [35] (Fig. 1D and Fig.…”
Section: Structural Studies and Refinement Of The Mechanistic Aspects Of The Enzymementioning
confidence: 54%
“…Moreover, comparison of the structures of complexes representing different steps of cyclisation with that of the apoenzyme indicated that the reaction progress is accompanied by conformational switches of the protein. The data led also to a detailed proposal of the mechanism of the cyclisation reaction [33][34][35].…”
Section: Structural Studies and Refinement Of The Mechanistic Aspects Of The Enzymementioning
confidence: 90%
See 2 more Smart Citations